“Chōsakan”: Research Judges Toiling at the Stone Fortress - Masako Kamiya (Washington University Law Review, 2011)
The Article describes the role of research judges in the Supreme Court of Japan. It outlines the functions of research judges under Article 57 of the Judiciary Act of 1947 which engage in research necessary for trial and adjudication of a court case. It highlights the supplementary provisions to Article 57 which include the appointment of instructors at the Legal Research and Training Institute (LRTI).
Keywords: Judicial process -- Research; Supreme Court justices (United States); Constitutional law -- Japan; Justice administration -- Japan; Japan. Daishin' in